Dialektyka i synteza. O Pascalowskiej filozofii człowieka - Błaszczyk, Marek (Studia Europaea Gnesnensia, 2015)
The study focuses on the characteristically Pascalian attempt at synthesizing of contradictory and intensely remote extremes of existence. Assuming the form of existential dialectics, the paradox of Pascalian vision refers in particular to the human, demonstrating the non-reducible tension between the intuitive (irrational) and the rational (panlogical); between the heart and the mind, between faith and knowledge. The conviction of human misery or the worldly vanity is fused here with the simultaneous sense of human greatness (the power of thought). The tension which therefore spans those dichotomous ontological-ontic dimensions is the determining factor of the constitution of individual existence.